2019
DOI: 10.4055/cios.2019.11.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of the Spinous Process Following Muscle-Preserving Posterior Lumbar Decompression via Sagittal Splitting of the Spinous Process

Abstract: Background In lumbar spinal stenosis, spinous process-splitting decompression has demonstrated good clinical outcomes with preservation of the posterior ligamentous complex and paraspinal muscles in comparison to conventional laminectomy, but the radiological consequence and clinical impact of the split spinous processes have not been fully understood. Methods Seventy-three patients who underwent spinous process-splitting decompression were included. The bone union rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Watanabe et al first described this technique in 2001 [17]. This technique is relatively largely used, especially in Japan, South Korea, and some centers in the US, Canada, and India, as described in the literature [18,11,10,16,5,7,9,3,6,1,8,4,19,13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Watanabe et al first described this technique in 2001 [17]. This technique is relatively largely used, especially in Japan, South Korea, and some centers in the US, Canada, and India, as described in the literature [18,11,10,16,5,7,9,3,6,1,8,4,19,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…3 This technique is relatively largely used, especially in Japan, South Korea, and some centers in the United States, Canada, and India, as described in the literature. 1,[4][5][6][7][8][9][10][11][12][13][14][15][16][17] The target is to be the least invasive, respecting the natural anatomy, preserving the bone continuity between spinous process and lamina and the integrity of the paraspinal muscles.…”
Section: Discussionmentioning
confidence: 99%
“…The authors’ modified SPSD was performed as previously reported. 11) It was based on the technique introduced by Watanabe et al 7) and modified by Cho et al, 13) Nomura et al, 10) and Hatta et al 14) Under general anesthesia, a posterior midline approach was performed, and the supraspinous and interspinous ligaments were sharply divided using a #10 scalpel blade. The proximal SP at the level to be decompressed was then split vertically and equally into the base using an ultrasonic blade ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…There have been many favorable clinical outcomes using SPSD modified by other surgeons; however, these are limited to short-term follow-up. 10 11) Furthermore, few studies have reported the possibility of delayed instability, reoperation rate, and effects on the clinical outcomes of union status of the split SP after SPSD. The purpose of the present study was to report the clinical and radiological mid-term outcomes of SPSD for DLSS.…”
mentioning
confidence: 99%
“…In this regard, this study aimed to investigate whether LBP as well as lower leg symptoms can also be improved in patients with CLSS by one-level lumbar decompression surgery, based upon the study results by other authors [18][19][20][21] that encroachment on the cauda equina itself can be a cause of LBP in CLSS.…”
Section: Introductionmentioning
confidence: 99%